Peran Posyandu dalam Meningkatkan Kualitas Kesehatan Ibu dan Anak di Desa Sukawening, Kabupaten Bogor - Nur Hafifah; Zaenal Abidin (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Village community health development is a non-governmental activity aimed at improving the quality of public health through improving the health and nutritional status. The success of the implementation of public health development that aims to improve the quality of public health in the village of Sukawening cannot be separated from the various supports and active roles carried out by the entire community. In this case the big role is the role of the Integrated Service Post (Posyandu) which is directly dealing with various social problems including health problems faced by the community. This study aims to determine the perception of the Sukawening Village community on the posyandu program, the role of the posyandu in improving the quality of maternal and child health, and posyandu as a community health center. The prioritization of the problems raised in this study is how the role of the Posyandu cadre in Sukawening Village in improving the quality of public health, especially mothers and children. Data collection was obtained through interviews and observations. Posyandu has an important role in improving the quality of maternal and child health through health service processes such as carrying out family planning services, nutrition, immunization, diarrhea prevention, and MCH. Sukawening village, especially RW 05, shows that the Posyandu program in the hamlet still needs to be evaluated. This is illustrated by the presence of toddlers who are still suffering from malnutrition. Keywords: Sukawening village, quality of public health, public health developments, posyandu.